2020
DOI: 10.1155/2020/9813970
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Crude Extracts of Artocarpus heterophyllus Seeds against Selected Diarrhoea-Causing Superbug Bacteria

Abstract: The current upsurge in resistance to conventional antibiotics, as well as high cost of orthodox medical treatment, called for the use of medicinal plants as an alternative therapy. This research was aimed at determining the antibacterial activity of Artocarpus heterophyllus seed extracts (Jackfruit as it is locally called) in the treatment of diarrhoea. Ethanolic and hexanolic seed crude extracts of the plant were screened for antidiarrhoeal activity against bacteria isolated from clinical samples (methicillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
6
13
1
Order By: Relevance
“…Ethanol solvents produced extracts with better antibacterial potential than the other solvents (Prastiyanto et al 2020d). These results are in line with the results of previous research on an ethanol extract of A. heterophyllus seeds which produced higher solubility of the active substances than the hexanes (Eve et al 2020). This can be attributed to the higher solubility of the seed phytochemical compounds of the seeds in ethanol than in hexane.…”
Section: Extract Yieldsupporting
confidence: 92%
See 3 more Smart Citations
“…Ethanol solvents produced extracts with better antibacterial potential than the other solvents (Prastiyanto et al 2020d). These results are in line with the results of previous research on an ethanol extract of A. heterophyllus seeds which produced higher solubility of the active substances than the hexanes (Eve et al 2020). This can be attributed to the higher solubility of the seed phytochemical compounds of the seeds in ethanol than in hexane.…”
Section: Extract Yieldsupporting
confidence: 92%
“…The results of this study can be concluded that the seed ethanol extract of three species of Artocarpus, namely A. lanceipolius, A. elasticus, and A. odoratissimus has the potential as antibacterial agents against MDR-E. coli. However, previous research by Eve et al (2020) showed that the ethanol extract of A. heterophyllus seeds which is a member of the genus Artocarpus did not have antibacterial activities against MDR-E. coli.…”
Section: The Antibacterial Activities Of Extracts Against Mdr-e Coli Agar Well Diffusion Assaymentioning
confidence: 91%
See 2 more Smart Citations
“…These antibacterial components may be bacteriostatic or bacteriocidal (Wu and Li 2016). Eve et al (2020) report that the susceptibility of gramnegative bacteria to antibacterial agents is due to the composition of various cell wall structures such as peptidoglycan, lipids, and cross-linking, which can greatly influence the penetration, binding, and activity of antimicrobial agents. P. aeruginosa is a gram-negative bacterium with a high-fat content in its cell walls (11-22%).…”
Section: Discussionmentioning
confidence: 99%